Mathematics The Study Of Numbers, Quantity And Space - Tracey Baptiste
This insightful guide to the history and basic concepts of mathematics reveals how math concepts helped to shape society--from the basic counting and units of measurement that facilitated commerce to the kind of surveying techniques and geometry that helped build the Egyptian pyramids. A chronological account of advancements in mathematics ranges Aristotle and al-Khwarizmi (who first used the term "algebra") to high-speed computers and their impact upon the teaching and understanding of mathematics. Readers will also find out how much of ancient arithmetic--like the 6 minute hour--is still part of our everyday life.